The Application of Fractal Art in the Teaching of Fine and Applied Arts in Higher Education - Khasanova Marjona Amirovna (Researchparks Publishing, 2021)
This article provides information on the role of fractal compositions in fine and applied arts, their rhythmic repetition in natural products and appearances. Fine arts classes cover the students’ teaching methods to use them in their independent work. It also reveals the student’s individual perception characteristics and ways to activate students' creative activity in the teaching of fractals in the teaching of fine and applied arts on the basis of experimental work with students.